Gambaran Tingkat Pengetahuan Masyarakat Pesisir Tentang Pertolongan Pertama Pada Korban Tenggelam Di Pantai Bulo, Tateli Weru - Tongka, Felianty; simbiring, Erika emina; Malara, Reginus (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2024)
Background. Drowning is one of the emergency cases that can threaten life and needs to be handled as soon as possible starting from helping victims when they are drowning until the victim reaches land, especially first aid in the critical period before the medical team arrives at the scene. Objective. To determine the level of knowledge of coastal communities about first aid for drowning victims. Methods. This study uses a type of quantitative research with a descriptive research design. The sample in this study consisted of 80 respondents. The instrument used is the coastal community knowledge instrument on how to first aid which has been tested valid with a calculated r value greater than r table (0.3610) and an alpha crombach value of 0.856 which is greater than 0.60. Results. This study shows the results of the level of community knowledge, namely 68 (85.0%) who are well informed and less knowledgeable as many as 12 (15.0%). Conclusion. Most of the community has good knowledge about first aid methods, but in some statement items regarding the first aid method, the respondents themselves are not knowledgeable. Keywords: BHD; Community Knowledge; Drowning; First Aid.